INTEGRASI KEADILAN RESTORATIF DALAM PROGRAM PEMBINAAN NARAPIDANA: MANFAAT MEDIASI KORBAN–PELAKU TERHADAP PENURUNAN RESIDIV - Andree Washington Hasiholan (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2025)
This study aimed to assess the effectiveness of integrating restorative justice into prisoner rehabilitation programs to reduce recidivism and improve social reintegration. The method used was a mixed-method design with a quasi-experimental quantitative approach comparing a group of prisoners who participated in victim-offender mediation within the rehabilitation program with a standard rehabilitation group, measured twelve months after release; and a qualitative approach through in-depth interviews with victims, prisoners, correctional officers, and community stakeholders, accompanied by a review of policy documents. Results showed that the mediation group experienced a decrease in recidivism, increased compliance, strengthened empathy, and improved social relationships compared to standard rehabilitation. Interviews revealed that success was influenced by the emotional readiness of the parties, the capacity of the facilitator, and family- and community-based post-release support. Conclusion: Integrating victim-offender mediation into correctional rehabilitation programs effectively reduces recidivism and improves the quality of reintegration, with the prerequisites of standardized implementation, cross-sectoral support, and protection mechanisms for victims; these findings provide the basis for policy formulation and long-term monitoring of outcomes.